Mast cell migration to Th2 stimulated airway smooth muscle from asthmatics. Issue 8 (6th April 2006) - Sutcliffe, A; Kaur, D; Page, S; Woodman, L; Armour, C L; Baraket, M; Bradding, P; Hughes, J M; Brightling, C E
Abstract : Background: Mast cell microlocalisation within the airway smooth muscle (ASM) bundle is an important determinant of the asthmatic phenotype. We hypothesised that mast cells migrate towards ASM in response to ASM derived chemokines. Methods: Primary ASM cultures from subjects with and without asthma were stimulated with interleukin (IL)-1β, IL-4, and IL-13 alone and in combination. Mast cell chemotaxis towards these ASM supernatants was investigated, and the chemotaxins mediating migration by using specific blocking antibodies for stem cell factor (SCF) and the chemokine receptors CCR3, CXCR1, 3 and 4 as well as the Gi inhibitor pertussis toxin and the tyrosine kinase inhibitor genistein were defined. The concentrations of CCL11, CXCL8, CXCL10, TGF-β, and SCF in the supernatants were measured and the effect of non-asthmatic ASM supernatants on the mast cell chemotactic activity of asthmatic ASM was examined. Results: Human lung mast cells and HMC-1 cells migrated towards Th2 stimulated ASM from asthmatics but not non-asthmatics. Mast cell migration was mediated through the combined activation of CCR3 and CXCR1. CCL11 and CXCL8 expression by ASM increased markedly after stimulation, but was similar in those with and without asthma. ASM supernatants from non-asthmatics inhibited mast cell migration towards the asthmatic ASM supernatant. Conclusion: Th2 stimulated ASM from asthmatics is chemotactic for mast cells. Non-asthmatic ASM releases a mediator or mediators that inhibit mast cell migration towards stimulated asthmatic ASM. Specifically targeting mast cell migration into the ASM bundle may provide a novel treatment for asthma.